Risk Factors for Pancreatic Stone Formation in Type 1 Autoimmune Pancreatitis: A Long-term Japanese Multicenter Analysis of 624 Patients. Issue 1 (January 2019) - Ito, Tetsuya; Kawa, Shigeyuki; Matsumoto, Akihiro; Kubota, Kensuke; Kamisawa, Terumi; Okazaki, Kazuichi; Hirano, Kenji; Hirooka, Yoshiki; Uchida, Kazushige; Masuda, Atsuhiro; Ohara, Hirotaka; Shimizu, Kyoko; et al.
Abstract : Objective: Autoimmune pancreatitis (AIP) has the potential to transform into chronic pancreatitis with pancreatic stone involvement. This retrospective investigation sought to clarify the risk factors for stone formation in type 1 AIP. Methods: Questionnaires on patients with type 1 AIP were sent to 22 high-volume medical centers across Japan to compare the clinical features of patients with and without pancreatic stone formation. Results: Of the completed records on 624 type 1 AIP patients, 31 (5%) had experienced pancreatic stones. Median follow-up duration was 1853 days. Bentiromide test values at diagnosis were significantly lower, and hemoglobin A1c values after corticosteroid treatment were significantly higher in patients with pancreatic stones. Imaging results disclosed that pancreatic atrophy and hilar or intrahepatic bile duct stenosis were significantly more frequent in patients with pancreatic stone formation. Pancreatic head swelling tended to be more frequent in this group as well. On the other hand, a shorter follow-up period was associated with the nonformation of pancreatic stones. Conclusions: The increased frequency of pancreatic head swelling in type 1 AIP patients exhibiting pancreatic stones indicated a propensity for pancreatic juice stasis with subsequent stone development and pancreatic dysfunction occurring over longer periods of disease duration.